Penunjang Keputusan Dalam Kelayakan Pemberian Kredit Motor Pada PT.Mandala Multifinance - Sarwindah Sarwindah; Marini Marini (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2020)
PT Mandala Multi Finance is a leasing company engaged in motorcycle loan services for loan applicants and takes advantage of loan interest payments. Basically, leasing companies recruit workers in the credit analyst section to analyze the ability to pay credit applicants and conduct field surveys to reduce credit defaults. ACredit Analyst is expected to work quickly and thoroughly in analyzing the amount of incoming credit applicant data so that it does not close the possibility of errors, such as miscalculations, errors in reading data, and others. Therefore, in an effort to help Credit Analysts in credit-worthy consumer decision-making activities, a computer-based system model is needed that can provide convenience in analyzing data, calculating credit applicants' assessment criteria, and helping processing data into information to make decisions about the problem. A decision support system is the right choice to help select credit applicants where the decision support system is designed using the AHP method, making the system using php programming language and MySQL database. It is expected that this decision support system can assist the work of leasing companies, especially in the Credit Analyst section in selecting credit applicants and can reduce errors in determining creditworthy consumers.